STRATEGI INVESTASI SAHAM DI BURSA EFEK INDONESIA DENGAN ANALISIS TEKNIKAL - Prihatiningsih Prihatiningsih; Embun Duriany; Aris Sunindyo; Moch Abdul Kodir (Politeknik Negeri Semarang, 2022)
The purpose this research are to know the movement of stock prices and determine the right time to buy, sell or hold shares of PT. Bank Rakyat Indonesia (Persero) Tbk in Januari – September 2021. This research method is descriptive method. The data used is secondary data in the form of daily time series data during February 2019 to January 2020. The analysis method uses technical analysis with the Moving Average (MA), Relative Strength Index (RSI) and Bollinger Band indicators. The results of the study show stock price movements and the right time to buy, sell and hold stocks which can be read using three indicators, namely Moving Average (MA), Relative Strength Index (RSI), and Bollinger Bands.